INVESTIGATION OF THE STRUCTURE OF PHTHALIMIDE-MODIFIED EPOXY MATRIX BY IR-SPECTRAL ANALYSIS - Sapronov, Oleksander; Cherniavskya, Tetiana; Sapronova, Annа; Sotsenko, Vitaliy; Antonio Bertem (Scientific Journal "Metallurgy", 2021)
Epoxy diane oligomer ED-20 was used as the main component for the for-mation of polymeric materials. It is characterized by a set of properties, namely: high adhesive strength, the possibility of curing at low temperatures, low shrink-age, manufacturability when applied to long-dimensional parts of a complex profile, the presence of a significant number of analogues, including in Ukraine. Pol-yethylene polyamine (PEPA) hardener was used to crosslink the epoxy oligomer at room temperature. Improving the properties of the epoxy matrix was achieved by using a modifier of phthalimide (isoindoline-1,3-dione) at a content of q = 0.25 pts.wt. at q = 100 pts.wt. of epoxy oligomer ED-20. The combination of components in the formation of polymeric materials was performed using ultrasonic dispersion. The operating frequency range was ν = 20…25 kHz, ultrasonic power N = 400… 1200 W. The amplitude of oscillations of the dispersant was A = 10… 20 μm, and the operating range was d = 20 mm. Under these parameters, ultrasonic treatment was performed for a time τ = 1.5±0.1 min, followed by cooling the composition to room temperature and the introduction of a hardener. The activity of the surface of the modifier was investigated by IR-spectral analysis. The main parameters of the IR spectra were determined using the computer program IRsolution. By the method of IR spectral analysis the presence of active groups: -NH-, O-H, С-H, C-N in the range of wave numbers ν = 3202…1971 cm–1, carbonyl C = O – at ν = 1759 cm–1, amide – in the range wave numbers of ν = 1604…1467 cm–1, amino groups – in the range of wave numbers ν = 648…794 cm–1, which indicates the catalytic activity of the modifier were found. Additionally, the dynamics of changes in the transmittance intensity, the relative area of the bands of the original and modified matrices were analyzed, which allowed to confirm the preliminary results of the study of the cohesive strength of polymers by increasing the number of chemical bonds in the volume of the polymer.